1979
DOI: 10.3758/bf03198791
|View full text |Cite
|
Sign up to set email alerts
|

A developmental investigation of selective attention to graphic, phonetic, and semantic information in words

Abstract: Second and fifth-grade and college-age subjects made similarity judgments on sets of three words that required attention to orthographic, phonetic, or semantic information. Accuracy and speed increased with age. Even the youngest subjects were able to perform the task of selecting a given feature of a word reasonably well. Differences in difficulty among the three tasks decreased with age, suggesting a developmental change (primarily between second and fifth grade) toward facility in extracting phonetic and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Edfeldt (1959), for example, suggested that children use phonological information when reading all words initially but that as words become more familiar they are identified on a visual basis. However, studies by Barron and Baron (1977), Condry, McMahon-Rideout, andLevy (1979), andRader (1975) failed to support this view because they provided evidence that even very young children were using visual, as opposed to phonological, codes in accessingmeaning.…”
Section: Discussionmentioning
confidence: 91%
“…Edfeldt (1959), for example, suggested that children use phonological information when reading all words initially but that as words become more familiar they are identified on a visual basis. However, studies by Barron and Baron (1977), Condry, McMahon-Rideout, andLevy (1979), andRader (1975) failed to support this view because they provided evidence that even very young children were using visual, as opposed to phonological, codes in accessingmeaning.…”
Section: Discussionmentioning
confidence: 91%
“…Van Orden, Pennington and Stone (1990) have argued that phonological coding continues to be used in word identification. They report data from Condry, McMahon-Rideout and Levy (1979) that involved synonym judgment (glad-happy). Distractor items included word pairs with a high degree of phonological similarity ( plate-wait ).…”
Section: Discussionmentioning
confidence: 99%
“…Probability-Efficiency Theory appears to give a better account of the data than Stage Theory. It can readily account for the findings of Rader (1975), Barron and Baron (1977), and Condry et al (1979), by assuming that the highly frequent and concrete content words used in these studies have a near-zero probability of being read via the phonological route, even by beginning readers.…”
Section: Phonological Recoding As a Back-up Mechanism In Reading Indimentioning
confidence: 93%
“…The final nail in the coffin of Stage Theory was a study reported by Condry, McMahon-Rideout, and Levy (1979), who used children from Grades 2 and 5 and adults. In this study, subjects were presented visually with a target word and had to decide which of two choice words were related to it in some particular way -either graphically, phonetically, or semantically.…”
Section: Phonological Recoding As a Back-up Mechanism In Reading Indimentioning
confidence: 99%
See 1 more Smart Citation